Identification of Water/Solid Flow Regime Using Ultrasonic Tomography - Yasmin, Abdul Wahab; Iskandar, Rizan Muhamad; Shahrizal, Saat (IEEE, 2012)
This paper details the development of suitable ultrasonic tomography system that can identify water and solid flow regime. This project presents the application of the ultrasonic tomography in the process and chemical industries. The transmission mode with fan shaped beam projection had been implemented. The system is designing non-invasively that mean the composition in the system can be monitored without disturbing the nature of process in the pipe. The transmission mode for sensing purpose was implemented by using 4 sensors for transmitters and 4 sensors for receivers where 4x4 projections were produced. This project is divided into two parts which are hardware and software. The hardware part is including electronic measurement circuit and fabrication of ultrasonic sensor. Beside, a software part is focusing a coding to microcontroller and circuit design. The data from experimental was analysed and it shows that it can be used to identify water and solid flow regime for ultrasonic tomography application.